Anti-Factor Xa–Based Anticoagulation during Extracorporeal Membrane Oxygenation: Potential Problems and Possible Solutions - Ranucci, Marco; Cotza, Mauro; Isgrò, Giuseppe; Carboni, Giovanni; Ballotta, Andrea; Baryshnikova, Ekaterina; for the Surgical Clinical Outcome REsearch (SCORE) Group (Seminars in Thrombosis and Hemostasis, 2020)
Choices for monitoring of unfractionated heparin (UFH) anticoagulation in extracorporeal membrane oxygenation (ECMO) patients include activated clotting time, activated partial thromboplastin time, reaction times of viscoelastic tests, and anti-factor Xa activity (between 0.3 and 0.7 IU/mL). Recent studies propose the anti-factor Xa to be the gold standard for monitoring UFH anticoagulation in ECMO. However, many extraneous factors combined question the utility of anti-factor Xa as the sole method of monitoring of UFH effects in ECMO. Anti-factor Xa is a chromogenic assay, which may be biased by the frequently elevated values of bilirubin and free hemoglobin in ECMO patients. The test may alternatively underestimate UFH effects in cases of low antithrombin values. More importantly, the anti-factor Xa assay is a plasma-based test which does not take into account the role of platelets and fibrinogen in forming a stable clot. Thrombocytopenia and platelet dysfunction are common features in ECMO patients, and underestimating their role may lead to over-anticoagulation, should only anti-factor Xa guiding be used to adjust the UFH dose. Conversely, fibrinogen is an acute phase protein, and some patients may experience high levels of fibrinogen during the ECMO course. In this case, an UFH monitoring based on anti-factor Xa is insensitive to this condition, although it may potentially be associated with thrombotic complications. Finally, the generally suggested range of 0.3 to 0.7 IU/mL is a somewhat arbitrary estimate, based on the desired range for treating and preventing thrombotic events in non-ECMO patients. In conclusion, anti-factor Xa may offer useful information on the real effects of UFH only when combined with a whole blood test capable of assessing the relative contribution of platelets and fibrinogen to clot formation.
Keywords: ECMO; anti-factor Xa; unfractionated heparin; viscoelastic tests